GENDER PREVALENCE IN CELIAC DISEASE - Javaed, Arsalan (ADVANCES IN BASIC MEDICAL SCIENCES, 2024)
Objective: There is no data showing which gender is predominantly affected by ce- liac disease (CD) available from Pakistan. This study was aimed to determine which gender is more affected by celiac disease. Material and methods: This cross sectional study was performed at Fatima Memo-rial Hospital, Lahore-Pakistan. 121 patients were recruited in the study according to the inclusion and exclusion criteria. Every patient went through upper gastro- intestinal endoscopy, as duodenal biopsy is the gold standard of the diagnosis. Histopathological evaluation was done according to Modified Marsh classifica- tion. Results: Out of 121 patients, 14 were diagnosed to have celiac disease. Out of 14 patients 11 (78.5%) were females and 3 (21.5%) were males. Conclusions: Females are predominantly associated with celiac disease with female to male ratio of3.6:1.